PENDAPATAN ASLI DAERAH DAN DANA ALOKASI UMUM TERHADAP ANGGARAN BELANJA MODAL DI PROVINSI SULAWESI UTARA - Pasaribu, Sandi Hasudungan; Tinangon, Jantje (Universitas Sam Ratulangi, 2015)
The local government allocated funds in the form of capital expenditure in the budget to increase fixed assets. Capital expenditure allocation is based on local needs for facilities and infrastructure, both for the smooth implementation of the tasks for the government and public facilities. Therefore, in an effort to improve the quality of public services, local government should change the composition of spending. During this shopping areas more used to spending relatively less productive routine. This study carried out in North Sulawesi Provincial Government by taking the data used for the study include data on local revenues, general allocation funds, and capital expenditure obtained from the Finance and Assets Management Agency of North Sulawesi Province. The purpose of this study was to determine how much influence of local revenues and a general allocation of funds towards capital expenditure budget in North Sulawesi. The analytical method used is quantitative descriptive analysis method that describes the position of research variables studied and the effect of one variable with other variables. Data analysis techniques to test the hypothesis performed using multiple linear regression analysis were processed through SPSS. Based on the results simultaneously (test F) indicates that the variable revenue (X1), and the general allocation fund (X2) significantly affects the capital expenditure budget in North Sulawesi. While for the results of research partially (t test) showed that variabels local revenues and a general allocation fund a significant effect on capital expenditure in North Sulawesi.